SIKAP BAHASA WANITA KARIR DAN IMPLIKASINYA TERHADAP PEMERTAHANAN BAHASA JAWA DI WILAYAH YOGYAKARTA - Yayuk Eni Rahayu (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2010)
This study aims to describe perceptions, attitudes, and factors influencing the use of Javanese among career women and the implications for the Javanese preservationin the Yogyakarta area. It was a survey study involving working women whose mother tongue was Javanese. The data were collected through a questionnaire andwere analyzed using the descriptive technique. The findings show that the career women’s perceptions are still positive. This is supported by the fact that they use Javanese in informal communicative situations. They use it in the communication with husbands, children, servants, and community members in informal situations, and colleagues in the workplace. It can be concluded that in informal communicative situations there has been no significant shift from Javanese into Indonesian among career women in the Yogyakarta area.